Microbiota Survey of Sliced Cooked Ham During the Secondary Shelf Life - Spampinato, Gloria; Candeliere, Francesco; Amaretti, Alberto; Licciardello, Fabio; Rossi, Maddalena; Raimondi, Stefano (Frontiers in Microbiology, 2022)
Sliced cooked ham packaged in modified atmosphere is a popular ready-to-eat product, subjected to abundant microbial contamination throughout its shelf life that can lead to deterioration of both sensorial properties and safety. In this study, the microbial load and the chemical-physical features of cooked ham of 5 producers were monitored for a period of 12 d after the opening of the packages (i.e., the secondary shelf life), during which the products were stored in a domestic refrigerator at 5.2 ± 0.6 °C. The sensorial properties presented a perceivable decay after 8 d and became unacceptable after 12 d. HPLC analysis and SPME-GC profiling of volatile metabolites indicated that lactic acid, ethanol, acetic acid, acetoin, 3-methyl-1-butanol, and 2-3 butanediol were the main metabolites that characterized the evolution of the analyzed cooked ham. The microbiota was monitored by 16S rRNA gene profiling and culture-dependent techniques. Already at the opening of packages, all the products presented high microbial load, generally dominated by lactic acid bacteria (LAB), with evident differences among the products. The increase of LAB somehow protected samples from abundant contamination by other bacteria, concurring to the evolution of more safe products. This role was exerted by numerous Latilactobacillus, Leuconostoc, and Carnobacterium species, among which the most frequently detected were L. sakei, L. sakei carnosum, L. mesenteroides, and C. divergens. Some products presented more complex communities that encompassed Proteobacteria such as Moellerella wisconsensis, Proteus hauseri, Brochothrix thermosphacta, and less frequently Pseudomonas, Erwinia, and Massilia. Opportunistic pathogenic bacteria such as Escherichia coli and Vibrio sp. were found in small quantities. The yeasts Kazachstania servazzii and Debaryomyces hansenii occurred already at 0 d, while various species of Candida (C. zeylanoides, C. sake, C. norvegica, and C. glaebosa) were abundant only after 12 d. These results indicated that the microbiological contaminants overgrowing during the secondary shelf life did not derive from environmental cross-contamination at the opening of the tray, but were already present when the packages were opened, highlighting the phases of production up to the packaging as those crucial in managing the safety risk associated to this product.